An Assessment of Reform Options For The Public Service Pension Fund In Uganda - Bogomolova, Tatiana (The World Bank, 2006)
This paper analyzes the future liabilities that the Ugandan Public Service Pensions Fund might accumulate under the provisions of the Pensions Act (CAP 286) unless it is reformed. It then discusses alternative reform options that can be used in designing an educated homegrown reform of the fund. The paper supports a hybrid (two-pillar) reform option composed of a small defined benefit scheme and a complementary defined contribution scheme, instead of a pure defined contribution (monopillar) reform option discussed by policymakers in the country. The main reason for this is related to the fact that hybrid and pure defined contribution reforms will have the same impact on reducing pension expenditure (for the same grandfathering rules and surplus in the first pillar). In addition, everything else being equal, the hybrid reform is likely to produce higher average replacement rates due to the redistributive and pooling properties of the small defined benefit pillar